2022
DOI: 10.4038/sljae.v4i1.75
|View full text |Cite
|
Sign up to set email alerts
|

The variation of abundance and fruit damage of <em>Bactrocera dorsalis</em> on two commercial varieties of Mangifera indica in main Bio-climatic Zones of Sri Lanka

Abstract: Bactrocera dorsalis Hendel, (Diptera: Tephritidae) is one of the serious fruit pests in South Asia. In Sri Lanka, there are dearth of past studies on the abundance and infestations of B. dorsalis on commercially important fruit varieties. Hence, the present study aimed to investigate the abundance of B. dorsalis adults and their infestation levels on Willard (Wld) and Karthakolomban (Kc) mango varieties grown in main bio-climatic zones of Sri Lanka. The study was conducted from September 2020 to February 2021 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Nevertheless, these studies did not concentrate on the oviposition preference of fruit flies in Sri Lanka. Recently, Wijekoon et al [25] reported that the fruit infestation by B. dorsalis was higher in the "Karutha kolumban" variety than the "Willard" variety in Sri Lanka. In another study, Wijekoon et al [26] showed that yellow "Willard" was preferred for oviposition by B. dorsalis over other color types.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, these studies did not concentrate on the oviposition preference of fruit flies in Sri Lanka. Recently, Wijekoon et al [25] reported that the fruit infestation by B. dorsalis was higher in the "Karutha kolumban" variety than the "Willard" variety in Sri Lanka. In another study, Wijekoon et al [26] showed that yellow "Willard" was preferred for oviposition by B. dorsalis over other color types.…”
Section: Introductionmentioning
confidence: 99%
“…Marasinghe et al (2018) also reported that the B. correcta was the dominant fruit fly than B. kandiensis and B. dorsalis in the survey at Kandy District, Sri Lanka. In terms of recent studies on fruit flies in Sri Lanka, Wijekoon et al (2021 reported the infestation variation of B. dorsalis on mango cultivations in different bio-climatic zones of Sri Lanka and the oviposition variation of B. dorsalis on `Willard` mango variety in Sri Lanka. Furthermore, in the diversity of Dacine fruit flies in selected mango cultivations in Southern Province, Sri Lanka was recorded by and that study indicated B. dorsalis as the highest abundant fruit fly species.…”
Section: Introductionmentioning
confidence: 99%